2009
DOI: 10.1016/j.molcel.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Set9-Mediated H4K20 Methylation by a PWWP Domain Protein

Abstract: Summary Methylation of histone H4 lysine 20 (H4K20me) is essential for recruiting checkpoint proteins 53BP1/Crb2 to DNA lesions and subsequent activation of a DNA damage checkpoint. In fission yeast, Set9 (spKMT5) catalyzes mono-, di- and tri-methylation of H4K20. However, the mechanisms that regulate Set9 function are poorly understood. Here we identified a PWWP domain protein Pdp1 as a Set9-associated factor. Pdp1 binds to histones and is required for Set9 chromatin localization. Yeast cells without Pdp1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
130
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(135 citation statements)
references
References 60 publications
(116 reference statements)
4
130
1
Order By: Relevance
“…It was only in 2009 that Wang and co-workers found out that the PWWP domain of the yeast protein Pdp1 directly binds to histone 4 lysine 20 monomethylation (H4K20me1) and that this interaction is crucial for the histone methyltransferase Set9 chromatin association (Wang et al 2009). These results first established a functional role for the PWWP domain as a methyl-lysine reader motif involved in epigenetic regulation.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was only in 2009 that Wang and co-workers found out that the PWWP domain of the yeast protein Pdp1 directly binds to histone 4 lysine 20 monomethylation (H4K20me1) and that this interaction is crucial for the histone methyltransferase Set9 chromatin association (Wang et al 2009). These results first established a functional role for the PWWP domain as a methyl-lysine reader motif involved in epigenetic regulation.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%
“…5). Mutations of the residues that compose the aromatic cage abolish methylated histone peptide binding (Wang et al 2009Vezzoli et al 2010;Maltby et al 2012;Smolle et al 2012;Wen et al 2014;Gilbert et al 2014;Guo et al 2014). Moreover, this aromatic cage is a common molecular architecture found in members of the Royal superfamily.…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as PWWP domains were recently shown to specifically interact with methylated histones, 17,18 it is tempting to speculate that EXPAND1, via its PWWP domain, may also preferentially associate with certain methylated histones in vivo. Given that histone methylation contributes to the epigenetic landscape and is intimately involved in numerous cellular processes, it will be of significant interest to identify this mark, which will offer further routes via which to dissect EXPAND1 functions, and to appreciate a fuller and a more comprehensive picture of the mammalian DNA damage response.…”
Section: Identification Of Expand1 As a Dna Damage Response Proteinmentioning
confidence: 99%
“…Compared with the MYND domain, essentially nothing was known about the three N-terminal putative chromatin readers. Previous studies indicated that PHD and BROMO domains are protein modalities that mainly recognize methylated and acetylated lysines located on the histone tails, respectively, whereas the PWWP domain has been suggested to primarily recognize the trimethylated histone H3 lysine 36 (29)(30)(31), as well as H4 lysine 20 (32,33). Therefore, the presence of these reader domains in BS69 suggests that BS69 may also recognize specific chromatin modification patterns, thus playing a bridging role between transcription and chromatin.…”
mentioning
confidence: 99%